VALORACIONES DE LOS ALUMNOS SOBRE EL USO DE LAS TIC EN EL AULA EN LOS CENTROS DE ENSEÑANZA SECUNDARIA DE LA CIUDAD DE TETUÁN - El Berdai, Majda Nniya; Torres, Juan Manuel Trujillo; Lucena, María Angustias Hinojo (European Scientific Journal, ESJ, 2015)
This study is part of a doctoral research on the process of the implementation and integration of ICT in the educational system in Morocco, where we intend to know the secondary schools students’ assessment on the use of ICT in the classroom during the teaching and learning process in the city of Tetuan. The total sample are four Preparatory Secondary Schools and four Qualifying Secondary Schools. We proceeded with the quantitative method for the collection and analysis of data and the final assessment of the respondents was negative.